1992
DOI: 10.1080/07328309208017809
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Antarctic Fish Antifreeze Glycoproteins by One- and Two-Dimensional NMR Spectroscopy

Abstract: The solution structure of antifreeze glycoproteins (AFGP's) of the polar fish Tetramatomus borchgrevinki has been investigated by 2D ' H NMR spectroscopy as well as molecular modeling calculations (MM2). The simple glycotripeptide repeating structure in the shorter AFGP's (fractions 7 & 8) makes the structural analysis amenable. The resonance assignments of AFGP's 7 & 8 were determined by two-dimensional NMR techniques (COSY, Relayed-COSY, Phase Sensitive DQCOSY, NOESY). Information about the protein secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Even though the study on synthetic AFGPs by Nishimura and coworkers presents a consistent picture the situation for naturally occurring AFGPs seems to be more complicated [167]. Structural studies on these molecules, isolated from fish, have a long history yielding conflicting interpretations [170][171][172][173][174][175].…”
Section: Antifreeze Glycoproteinsmentioning
confidence: 99%
“…Even though the study on synthetic AFGPs by Nishimura and coworkers presents a consistent picture the situation for naturally occurring AFGPs seems to be more complicated [167]. Structural studies on these molecules, isolated from fish, have a long history yielding conflicting interpretations [170][171][172][173][174][175].…”
Section: Antifreeze Glycoproteinsmentioning
confidence: 99%
“…3) are not due to a structural difference. 2D NMR studies (300 MHz) [89] allowed further refinement of this data and measurement of amide exchange rates which ruled out significant strong hydrogen bonding involving the amide protons in aqueous solutions. Comparison of AFGP amide vibrational frequencies with those observed and calculated for beta and gamma‐turns in other peptides suggests that AFGPs contain substantial turn structure [90] while NMR studies on model glycopeptides showed an intramolecular hydrogen bond between the amide proton of N ‐acetylgalactosamine and the carbonyl oxygen of the Thr to which the sugar is attached [91].…”
Section: Solution Conformationmentioning
confidence: 99%
“…Furthermore, AFGP-8 is the only AFGP found in the tissue samples outside the blood stream (Burcham et al, 1986;Mulvihill et al, 1980). The x-ray structure for AFGP-8 is not yet known, but experimental work on the structural elucidation of this AFGP using a variety of experimental techniques, such as nuclear magnetic resonance (NMR) and ultra-ultraviolet circular dichroism (CD) (Bush et al, 1981(Bush et al, , 1984Rao and Bush, 1987;Filira et al, 1990;Dill et al, 1992;Mimura et al, 1992;Lane et al, 1998) have yielded rather confusing and conflicting messages, from the standpoint of structural biology. NMR work by Bush et al and Lane et al suggested that, because NMR spectra show an absence of long-range coupling, AFGP-8 does not have well-defined structure at all.…”
Section: Introductionmentioning
confidence: 99%